Information Technology in the Modeling of Dry Gas Seal for Centrifugal Compressors - Rozova, Lyudmila; Martynenko, Gennadii (My University, 2020)
The developed specialized software package for computer modeling of dry gas seals for the rotors of centrifugal compressors is presented. This software package implements the mathematical model that describes improved methodology for seals modeling and solving under steady-state compressor operating conditions. It allows to make a model of working gap between the seal rings, which changes under the influence of gas pressure and temperature. This improved computer modeling can provide the reliable operation of dry gas seals. The developed software package has been tested on real constructions of dry gas seals with different types of groves. The results of test solutions were compared with available in literature and experimental studies.
Keywords: computer simulation; engineering software; compressor gas seals